Prevalencia de marcadores serológicos en hemodonantes en banco de sangre del Hospital III Iquitos-EsSalud 2015 a 2021 - Vásquez Espinar, Gilberto Bianor (2023)
Objective: To know the prevalence of serological markers in blood donors at the Blood Bank of Hospital III Iquitos -EsSalud from 2015 to 2021. Materials and methods: The research design was observational, descriptive, retrospective. The population consisted of 8727 replacement blood donors. An information collection sheet based on secondary data was applied. Results: The highest percentage of respondents were male (10.47%), aged 35 to 43 years (3.93%), independent (6.31%), cohabiting (5.69%), urban origin (7.65%). The most frequent reactive serological markers were anti-HBc (7.32%), anti-Treponema pallidum (2.58%), anti-HTLV I/II (0.84%). There is a relationship between anti-HBc (p<0.05), anti-Treponema pallidum (p<0.05), with age, sex, origin, occupation; and also anti-HBc (p<0.05) was related to marital status. Agp24 and anti-HIV 1/2 (p=0.003), anti-HTLV I/II (p=0.024), HBsAg (p=0.018) and anti-Trypanosoma cruzi (p=0.046) showed a relationship with the origin. Conclusions: The prevalence of reactive serological markers in donors from the Blood Bank of Hospital III Iquitos-EsSalud was 13.76%. The most prevalent were for anti-HBc, anti-Treponema pallidum and anti-HTLV I/II. These are related to sociodemographic variables.